Implementation of Strategic Management Practices in the Malaysian Construction Industry - Abu Hassan Abu Bakar; Muhammad Asim Tufail (Corresponding author); Mohamad Nizam Yusof; Wiwied Virgiyanti (Pakistan Journal of Commerce and Social Sciences, 2011)
Strategic Management is a concept that concerns with making decisions and taking corrective actions to achieve long term targets and goals of an organization. The importance of strategic management in a firm can be answered by analyzing relationship between strategic management and organizational performance. Generally strategic management practices can improve efficiency in various organizations. The objective of this paper is to study the practice of strategic management in construction companies in Malaysia. Questionnaires were distributed to 300 large construction companies listed under G7 groups classified by Construction Industry Development Board (CIDB). The response rate of the survey is 26% or that 78 construction companies replied. The findings of the research showed that most of the firms practicing strategic managementhave a clear objective, a winning strategy to achieve the objective and a sound mission statement to guide the organization towards success.